Analisis Kelayakan Usahatani Padi Sawah Tadah Hujan di Nagari Pasia Palangai Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan - Gusrati; Amnilis; Mardian Lona Putra (Jurnal Research Ilmu Pertanian, 2023)
The purpose of this study was to determine the characteristics of lowland rice farmers and analyze the feasibility of rainfed lowland rice farming in Nagari Pasia Palangai, Ranah Pesisir District, Pesisir Selatan Regency. This research was conducted from January to February 2021. The research method used was descriptive method with a population of 155 people and a total sample of 61 people. The data were analyzed descriptively, qualitatively and quantitatively, by analyzing the feasibility of farming. The results showed the characteristics of lowland rice farmers in Nagari Pasia Palangai, Ranah Pesisir District, Pesisir Selatan Regency, the dominant age of farmers was 45-50 years (40.98%), elementary education (50.82%), farming experience 21-30 years (37, 70%) and 2-4 family dependents (80.33%), land area >0.50 Ha (54.02%). The average production of rainfed lowland rice farming in Nagari Pasie Palangai is 4,647 kg/MT, revenue is Rp.23,233,890/MT, total production costs are Rp. 8,200,740/MT, income is Rp. 18,587,924/Ha/MT and a profit of Rp. 15,033,150/Ha/MT. Rainfed lowland rice farming in the research location is feasible with an R/C ratio value of 2.8. BEP production of 1,640 kg with a selling price of Rp 5,000 and BEP price of Rp 1,765.